Adiaphora and Indeterminacy of the Law: On the Tomistic Doctrine of the Determinatio and its Constructive and Completive Role in the Scholastics - Contreras, Sebastián (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
This paper analyzes the thomistic concept of determination. For Aquinas, determination isone of the modes of derivation of the human law from natural law, and particularly the manner in which the civil or positive law is derived. The scholastics retake the reflection of Aquinas on this issue, and enrich his thought with new ideas and concepts, especially Luis de Leon and Domingo de Soto, theauthors on whom we focused our research.
Keywords: determinatio; Aquinas; natural just; positive just; Luis de León; Domingo de Soto.